Annual report - AMMB Holdings Berhad; AmBank group (Kuala Lumpur : AMMB Holdings Berhad, 2006)
Annual report for the year 2006 by AMMB Holding Berhad, group of AmBank
PTSL : 2005, 2006, 2008, 2009
System requirements : Windows pentium III or later, 64MB RAM, windows 95/98/ME/2000/XP, sound card and speakers, 4X speed CD-ROM drive or faster, high color (16 bit) at a resolution of 800 X 600 pixels ; power macintosh or later, 64 MB RAM, MAC OS 8.5 or later, 4X speed CD-ROM drive or faster, high color (16 bit) at a resolution of 800 X 600 pixels
Keywords: AMMB Holdings Berhad -- Periodicals; Banks and banking -- Malaysia -- Periodicals; Banks and banking -- Periodicals; Commercial finance companies -- Malaysia -- Periodicals